Boosting ovarian cancer immunotherapy via discoidin domain receptor 2 blockade and CD28 x mucin 1 bispecific antibodies - Martina Kunkl; Silvia Malatesta; Flavia Ottavi; Ilenia Masi; Manolo Sambucci; Virginia Vigiano Benedetti; Maria Egle De Stefano; Martina Leopizzi; Maria Teresa Fiorillo; Marco Rossi; Francesco Mura; Anacleto Proietti; et al. (BMC Medicine, 2026)
Abstract Background Serous ovarian carcinoma (SOC) is a highly aggressive gynaecological malignancy with frequent relapse and the development of chemoresistance. A major feature of SOC tumour microenvironment is the accumulation of dense collagen fibres, which promote tumour progression and immune evasion. Discoidin domain receptor 2 (DDR2), a collagen-binding receptor tyrosine kinase activated by fibrillar collagens, mediates extracellular matrix-associated signalling involved in tumour progression and immune exclusion. However, its role in limiting antitumour immunity and contributing to immunotherapy resistance in SOC remains poorly understood. Methods We investigated the impact of DDR2 blockade on SOC-specific T cell activity and on the efficacy of recombinant bispecific antibodies (BsAbs) targeting CD28 and mucin 1 (MUC1). SOC-specific T cells were generated from healthy donor peripheral blood mononuclear cells and assessed for recruitment, activation, and cytotoxicity against low-grade (OVCA433) and high-grade (OVCAR3) SOC cell lines under different treatment conditions. Results DDR2 inhibition enhanced SOC-specific T cell responses by remodelling the collagen matrix, favouring their recruitment, activation and cytotoxic activity against both low- and high-grade SOC cells. Moreover, combined treatment with DDR2 blockade and CD28xMUC1 BsAbs significantly increased the recruitment of SOC-specific T cells, granzyme B release, caspase-3 activation, and cytokine production. Conclusions DDR2 blockade mitigates collagen-mediated immune exclusion and enhances the efficacy of CD28xMUC1 BsAb-based immunotherapy in SOC models. These findings provide a mechanistic rationale for further investigation of combined DDR2 targeting and CD28×MUC1 costimulatory strategies to improve ovarian cancer immunotherapy.